Synthesis and structures of morpholine substituted new vic-dioxime ligand and its Ni(II) complexes - Durmus, M; Ahsen, V; Luneau, D; Pécaut, J (Elsevier Science Sa, 2004)
N,N'-bis[4-(2-aminoethyl)morpholino]glyoxime (H2L) (Fig. 1), has been prepared in various yields using three different methods. The most efficient of these methods is the technique of microwave irradiation. The crystal structures of H2L, and of two nickel(II) complexes 1 and 2 have been determined by single crystal X-ray diffraction. Both nickel(II) complexes have a metal-ligand ratio of 1:2 in which the ligand coordinates through the two nitrogen atoms as do most vic-dioximes. The nickel(II) complexes are either hydrogen (1) or boron diphenyl bridged (2). Complex 1 was synthesized by reacting H,L with nickel(II) chloride in refluxing ethanol. Complex 2 was prepared at room temperature in an ethanol solution containing excess NaBPh4. Elemental analyses, NMR(H-1, C-13), IR and mass data are also presented. (C) 2003 Published by Elsevier B.V.
Keywords: vic-dioximes; nickel(II) complexes; glyoximes